PERISTIWA MOUNT FELIX DI BENGKULU (Perjuangan rakyat Bengkulu melawan penjajah Inggris 27 Desember 1807) - Ahmad Suharlan; Ridwan Melay; Kamaruddin Kamaruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The Mount Felix event in Bengkulu was the struggle of the people of Bengkulu against the British Company under Resident Thomas Parr. Thomas parr in Bengkulu promoted a cruel and inhuman system of cultivation of coffee in a cruel and inhuman way, the people took their revenge one night on December 27, 1807. On that night the Bengkulu people's armed forces of various tribes that perpetrated the raid were about 300 stronger in number Thomas Parr's resting place in Mount Felix under the command of Prince Natadirja III, Rajo Lelo and Adipati Sukarami. Regardless of what happened in the future without wasting time Resident Thomas Parr had to pay for his politics with his own life, the three warlords instantly killed Thomas Parr by stabbing and having his head severed and taken away without harassing Murray, Parr's wife and Parr's children. The purpose of this research is to know the background of the events in Mount, to know the struggle of the people of Bengkulu in the events in Mount Felix, to know the impact caused by events in Mount Felix. The method used in this research is historical method. The location of his research in Bengkulu City, Bengkulu Province. The research time starts from proposal seminar up to Thesis exam. Data collection techniques used are observation techniques, library techniques, documentation techniques. From the result of the research, it can be concluded that Mount Felix event in Bengkulu is a fact of Bengkulu people's hard, independent, self-respecting, and upholding their customs and customary laws that eradicate the tyranny of British colonialists.Keywords: Incident, Mount Felix, People's struggle against the British invaders